Worldwide Survey on Digital Assistive Technology (DAT) Provision - Isabel Margot-Cattin; Anne Deblock-Bellamy; Julie Wassmer; Ritchard Ledgerd; Claudia von Zweck; null World Federation of Occupational Therapists (WFOT) (Occupational Therapy International, 2024)
Occupational therapists have long been involved in assistive technology (AT) provision worldwide. AT is recognized by the World Health Organization (WHO) to enhance functioning, independence, and autonomy and ultimately promote well-being for people living with disabilities. With the digitalisation of societies, the everyday lives and occupations of individuals are changing, becoming more reliant on digital solutions. The development of digital assistive technology (DAT) also offers opportunities for people with disabilities to access, interact, and pilot the digital world. However, we do not know how occupational therapists are involved in DAT provision worldwide. A survey was conducted in the global occupational therapist’s community in June 2022 to describe DAT provision and the factors influencing it. Occupational therapy practitioners were included (n=660) in the analysis. In DAT provision, occupational therapists mostly provide advice to people, assess their needs, provide instruction or training, prescribe DAT, and fit DAT to people and their environment. The clients served through DAT provision are most frequently people with neurological impairments, chronic illnesses, sensory impairments, and older people. The reasons for providing DAT focus on education, work, school, and leisure. It is expected that DAT provision will enhance independence, self-esteem, occupational participation, and social relationships. Issues faced by occupational therapists when providing DAT are costs of product and funding schemes, sufficient knowledge, and access to knowledge sources. Survey respondents are mostly from Western countries with access to the Internet and the digital world, including having digital literacy, highlighting the digital divide that exists between world regions and countries, but also within countries worldwide. There is a need to continue research to better understand the issues related to digitalisation and the digital participation of people living with disabilities.